(untitled) (Scientific journal of the Fergana State University, 2024)
In the Turkestan region jadid progressives considered women to be educated, educated, an important factor in raising a worthy harmonious generation that can contribute to the prosperity of the country, as well as ensuring harmony in the family. They encouraged their contemporaries, fathers of the nation, to educate their daughters, to reform their education. In this article, the views of the enlightenment on the education of women in the Turkestan region at the end of the XIX – first quarter of the XX centuries are covered by historical analysis on the basis of articles, works on the pages of the periodical press.